Enhancement of up-conversion emission and emerging cool white light emission in co-doped Yb3+/ Er3+: Li2O-LiF-B2O3-ZnO glasses for photonic applications. Issue 14 (1st October 2017) - Vijayalakshmi, L.; Kumar, K. Naveen; Hwang, Pyung; Kaur, Gagandeep
Abstract: A series of co-doped (Yb 3+ /Er 3+ ): Li2 O-LiF-B2 O3 -ZnO glasses were prepared by standard melt quenching technique. Structural and morphological studies were carried out by XRD and FESEM. Phonon energy dynamics have been clearly elucidated by Laser Raman analysis. The pertinent absorption bands were observed in optical absorption spectra of singly doped and co-doped Yb 3+ /Er 3+ : LBZ glasses. We have been observed a strong up-conversion red emission pertaining to Er 3+ ions at 1.0 mol% under the excitation of 980 nm. However, the up-conversion and down conversion (1.53 µm) emission intensities were remarkably enhanced with the addition of Yb 3+ ions to Er 3+ : LBZ glasses due to energy transfer from Yb 3+ to Er 3+ . Up-conversion emission spectra of co-doped (Yb 3+ /Er 3+ ): LBZ glasses exhibits three strong emissions at 480 nm, 541 nm and 610 nm which are assigned with corresponding electronic transitions of 2 H9/2 → 4 I15/2, 4 S3/2 → 4 I15/2 and 4 F9/2 → 4 I15/2 respectively. Consequently, the green to red ratio values (G/R) also supports the strong up-conversion emission. The Commission International de E′clairage coordinates and correlated color temperatures (CCT) were calculated from their up-conversion emission spectra of co-doped (Yb 3+ /Er 3+ ): LBZ glasses. The obtained chromaticity coordinates for optimized glass (0.332, 0.337) with CCT value at 5520 K are very close to the standard white colorimetric point in cool white region. These results could be suggested that the obtained co-doped (Yb 3+ /Er 3+ ): LBZ glasses are promising candidates for w-LEDs applications.